INFORMATION PROCESSING DEVICE, CONTROL TERMINAL, INFORMATION PROCESSING METHOD, AND COMPUTER PROGRAM - YOSHIOKA, Toshiya; MATSUMOTO, Shintaro; NISHIMURA, Shigeki (2023)
An information processing device according to one embodiment of the present disclosure comprises: an acquisition unit that acquires probe information of a probe vehicle passing along an entering passage toward an intersection; and a control unit that executes dynamic control for determining, at each prescribed control cycle, signal control parameters to be adopted for the intersection. The intersection is not subject to a remote control by a central device, the signal control parameters include splits to be adopted for the intersection, and the dynamic control includes dynamic split control for updating the splits on the basis of a traffic index on the entering passage calculated from the probe information. Conformément à un mode de réalisation, la présente invention concerne un dispositif de traitement d'informations qui comprend : une unité d'acquisition qui acquiert des informations de sonde d'un véhicule-sonde passant le long d'un passage d'entrée vers une intersection ; et une unité de commande qui exécute une commande dynamique pour déterminer, à chaque cycle de commande prescrit, des paramètres de commande de feu à adopter pour l'intersection. L'intersection n'est pas soumise à une commande à distance par un dispositif central, les paramètres de commande de feu comprennent des divisions à adopter pour l'intersection, et la commande dynamique comprend une commande de division dynamique pour mettre à jour les divisions sur la base d'un indice de trafic sur le passage d'entrée calculé à partir des informations de sonde. 本開示の一態様に係る装置は、交差点への流入路を通行するプローブ車両のプローブ情報を取得する取得部と、前記交差点に適用する信号制御パラメータを所定の制御周期ごとに決定する動的制御を実行する制御部と、を備える情報処理装置であって、前記交差点は、中央装置による遠隔制御の対象ではない交差点であり、前記信号制御パラメータは、前記交差点に適用するスプリットを含み、前記動的制御は、前記プローブ情報から算出される前記流入路の交通指標に基づいて、前記スプリットを更新するスプリットの動的制御を含む。